Memoria and the Lust Disease: An Augustinian Enquiry into Post-Conversion Sexual Habit - Laskaris, Ernie (The Evangelical quarterly, 2020)
It is increasingly difficult for Christians in the twenty-first century West to avoid the influence of a hypersexualised culture, particularly for Christians with memories of a sexual life (outside of marriage) prior to conversion. The classic case of this category is that of Augustine, who spoke of'the images of such things as [his] sexual habits had fixed' in his memory, a symptom of what called 'the lust disease'. In his Confessions, he engages in a philosophical enquiry into the mysteries of the memory, searching for God in the 'place' of memory, but concluding that the incorporeal God cannot be found in a 'place'. While it is impossible to erase memories of one's pre-conversion sexual life through one's volition, Augustine found that it is possible to 'displace' memory so as to find the unplaceable God. In this way, one might see greater success in the struggle against residual, post-conversion concupiscence.